Single-embryo transfer reduces clinical pregnancy rates and live births in fresh IVF and Intracytoplasmic Sperm Injection (ICSI) cycles: a meta-analysis - Baruffi, Ricardo L. R.; Mauri, Ana L.; Petersen, Claudia G.; Nicoletti, Andreia; Pontes, Anaglória [UNESP]; Oliveira, Joao Batista A. [UNESP]; Franco, Jose G. [UNESP] (Biomed Central Ltd., 2009)
Background: It has become an accepted procedure to transfer more than one embryo to the patient to achieve acceptable ongoing pregnancy rates. However, transfers of more than a single embryo increase the probability of establishing a multiple gestation. Single-embryo transfer can minimize twin pregnancies but may also lower live birth rates. This meta-analysis aimed to compare current data on single-embryo versus double-embryo transfer in fresh IVF/ICSI cycles with respect to implantation, ongoing pregnancy and live birth rates.Methods: Search strategies included on-line surveys of databases from 1995 to 2008. Data management and analysis were conducted using the Stats Direct statistical software. The fixed-effect model was used for odds ratio (OR). Fixed-effect effectiveness was evaluated by the Mantel Haenszel method. Seven trials fulfilled the inclusion criteria.Results: When pooling results under the fixed-effect model, the implantation rate was not significantly different between double-embryo transfer (34.5%) and single-embryo transfer group (34.7%) (P = 0.96; OR = 0.99, 95% CI 0.78, 1.25). on the other hand, double-embryo transfer produced a statistically significantly higher ongoing clinical pregnancy rate (44.5%) than single-embryo transfer (28.3%) (P < 0.0001; OR: 2.06, 95% CI = 1.64,2.60). At the same time, pooling results presented a significantly higher live birth rate when double-embryo transfer (42.5%) (P < 0.001; OR: 1.87, 95% CI = 1.44,2.42) was compared with single-embryo transfer (28.4%).Conclusion: Meta-analysis with 95% confidence showed that, despite similar implantation rates, fresh double-embryo transfer had a 1.64 to 2.60 times greater ongoing pregnancy rate and 1.44 to 2.42 times greater live birth rate than single-embryo transfer in a population suitable for ART treatment.